How to Attract Women in STEM and Help Them Become Successful: The Review of Practices of Overcoming Gender Stereotypes - N. G. Maloshonok; I. A. Shcheglova; K. A. Vilkova; M. O. Abramova (Moscow Polytechnic University, 2022)
Gender imbalance among students in STEM (Science, Technology, Engineering and Mathematics) is a worldwide problem leading to negative social and economic consequences. Despite the widespread "myth of gender equality" in Russia, this problem is also relevant for our country. The share of male students in most STEM fields in Russian universities significantly exceeds the share of female students, especially in engineering and technical fields. The article is aimed at analyzing the existing experience of combating gender stereotypes in STEM educational programs. It provides an overview of seven types of practices: 1) informing girls about gender stereotypes and their negative consequences; 2) practices aimed at developing "growth mindset"; 3) influence through "role models" and the formation of friendship networks based on interest in STEM; 4) class composition management; 5) organization of active learning; 6) emphasis on the public benefit of career in STEM; 7) creating a positive climate through working with stereotypes of male teachers and students. The article also discusses the applicability of these practices in the Russian educational context.